Construction of Three‐Dimensional DNA Hydrogels from Linear Building Blocks1. Issue 32 (25th June 2014) - Nöll, Tanja; Schönherr, Holger; Wesner, Daniel; Schopferer, Michael; Paululat, Thomas; Nöll, Gilbert
Abstract A three‐dimensional DNA hydrogel was generated by self‐assembly of short linear double‐stranded DNA (dsDNA) building blocks equipped with sticky ends. The resulting DNA hydrogel is thermoresponsive and the length of the supramolecular dsDNA structures varies with temperature. The average diffusion coefficients of the supramolecular dsDNA structures formed by self‐assembly were determined by diffusion‐ordered NMR spectroscopy (DOSY NMR) for temperatures higher than 60 °C. Temperature‐dependent rheological measurements revealed a gel point of 42±1 °C. Below this temperature, the resulting material behaved as a true gel of high viscosity with values for the storage modulus G′ being significantly larger than that for the loss modulus G′′. Frequency‐dependent rheological measurements at 20 °C revealed a mesh size (ξ) of 15 nm. AFM analysis of the diluted hydrogel in the dry state showed densely packed structures of entangled chains, which are also expected to contain multiple interlocked rings and catenanes.